Use of laboratory techniques in the evaluation of ruminant production systems in semi-arid environments (Research, Society and Development, 2021)
The choice of the type of animal production system is an important factor, not only when it comes to the availability of food for the animals, but also because of the impacts that this activity can cause to the environment. The semi-arid region of the Brazilian Northeast has annual temperature averages of 23 to 27ºC and a hot, dry climate with rainfall of 280 to 800 mm. These edaphoclimatic conditions hinder regional livestock farming, given that a large part of the herd is raised in extensive management with the main food source coming from Caatinga plants. Therefore, it is necessary to study production systems adapted to these environments, ensuring the feeding of animals, especially in the face of global warming scenarios. In this perspective, through the chemical composition of food, laboratory techniques are the most used for this purpose, favoring the choice of forage capable of improving the feed efficiency of the animal, besides allowing the knowledge of its contribution to the production of enteric methane (CH4) in ruminant animals. Since, depending on the feed, methanogenic bacteria in the rumen can intensify CH4 production. Therefore, laboratory equipment and methods are continuously resorted to in preparing solutions and conducting chemical analyses of feed. In view of the above, this study aimed to describe the steps of laboratory techniques used in the evaluation of ruminant production systems in semi-arid environments.